Metallurgical Aspects of Laser Surface Processing of PM Cr-V Ledeburitic Steel. (13th December 2010) - Jurči, Peter; Cejp, Jiři; Brajer, Jan
Abstract : The Vanadis 6 ledeburitic-type steel was laser surface remelted. Microstructural changes and hardness in laser affected material were investigated using light microscopy, SEM, and EDS-microanalysis. It was found that the laser surface melting and subsequent rapid solidifying led to softening of the material, due to presence of retained austenite. The melting of the material begins with the transformation of M7 C3 -carbide into a liquid and finishes via the dissolution of primary solid solution grains. The solidification proceeded in a reverse manner while the eutectics became often so-called degenerous form.